Reconstructed Southeastern European Identities in the Tourist Western World: Phenomenological Research (Journal of Advanced Research in Social Sciences, 2025)
The article analyzes the experiences of modern Southeastern Europeans regarding social and economic mobility in Western tourist areas. It aims to investigate Southeastern European seasonal workers who have not remained silent, even after their visas expired in developed countries. This study seeks to understand how these Southeastern European identities are constructed while working as immigrant students, conceptualizing language learning, and contributing as multicultural members in a service-oriented tourist society. In higher education, within a democratic paradigm, the content of ethnographic and global sociolinguistic literature is supported by cultural capital, where constructed identities are understood from a critical perspective. This study uses qualitative data underpinning Husserl’s phenomenology. Qualitative methods include interview protocols, ethnographic observations, and individual narratives. Overarching themes from seven semi-experienced individuals in Southeastern Europe who faced accountability, intercultural adaptation, and educational integration reflect the progressive education that evolved from home to the new tourist world abroad. The findings revealed three main themes: individual acculturation, evolved identity view, and social incisiveness in a multicultural society. Furthermore, Southeastern European immigration rises daily and collaboratively, opening new global perspectives in educational policies, global citizenship education, and social justice curricula within the hospitality industry, where tourists' identities seek protection for their initial Western jobs. These findings suggest that, through an experiential curriculum, ESL learners integrate Southeastern potential tourist workers and become students to understand social and economic perspectives while incorporating them into corporate higher education. The implications contemplate how tourist identity is formed, transformed, and plays a significant role in modern society, with limited potential in the Western tourist world. The policy challenges of higher education for immigrants, such as those from Southeastern Europe affected by the brain drain phenomenon, emphasize social injustice, language barriers, and cultural anxiety. Therefore, higher education policy acknowledges this vulnerable group of Southeastern individuals and creates educational pathways for social and emotional support.